Quantitative proteomics reveals a broad‐spectrum antiviral property of ivermectin, benefiting for COVID‐19 treatment. Issue 4 (22nd September 2020) - Li, Na; Zhao, Lingfeng; Zhan, Xianquan
Abstract: Viruses such as human cytomegalovirus (HCMV), human papillomavirus (HPV), Epstein–Barr virus (EBV), human immunodeficiency virus (HIV), and coronavirus (severe acute respiratory syndrome coronavirus 2 [SARS‐CoV‐2]) represent a great burden to human health worldwide. FDA‐approved anti‐parasite drug ivermectin is also an antibacterial, antiviral, and anticancer agent, which offers more potentiality to improve global public health, and it can effectively inhibit the replication of SARS‐CoV‐2 in vitro. This study sought to identify ivermectin‐related virus infection pathway alterations in human ovarian cancer cells. Stable isotope labeling by amino acids in cell culture (SILAC) quantitative proteomics was used to analyze human ovarian cancer cells TOV‐21G treated with and without ivermectin (20 μmol/L) for 24 h, which identified 4447 ivermectin‐related proteins in ovarian cancer cells. Pathway network analysis revealed four statistically significant antiviral pathways, including HCMV, HPV, EBV, and HIV1 infection pathways. Interestingly, compared with the reported 284 SARS‐CoV‐2/COVID‐19‐related genes from GencLip3, we identified 52 SARS‐CoV‐2/COVID‐19‐related protein alterations when treated with and without ivermectin. Protein–protein network (PPI) was constructed based on the interactions between 284 SARS‐CoV‐2/COVID‐19‐related genes and between 52 SARS‐CoV‐2/COVID‐19‐related proteins regulated by ivermectin. Molecular complex detection analysis of PPI network identified three hub modules, including cytokines and growth factor family, MAP kinase and G‐protein family, and HLA class proteins. Gene Ontology analysis revealed 10 statistically significant cellular components, 13 molecular functions, and 11 biological processes. These findings demonstrate the broad‐spectrum antiviral property of ivermectin benefiting for COVID‐19 treatment in the context of predictive, preventive, and personalized medicine in virus‐related diseases. Abstract : 1. This study sought to identify ivermectin‐related virus infection pathway alterations in human cells. 2. Quantitative proteomics revealed that ivermectin‐related proteins are involved in four statistically significant antiviral pathways, including human cytomegalovirus (HCMV), human papillomavirus (HPV), Epstein–Barr virus (EBV), human immunodeficiency virus 1 (HIV1), and COVID‐19 infection pathways. 3. We identified 52 severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2)/COVID‐19‐related protein alterations when treated with and without ivermectin, and these proteins were involved in cytokines and growth factor family, MAP kinase and G‐protein family, and HLA class proteins. 4. These findings demonstrate the broad‐spectrum antiviral property of ivermectin benefiting for COVID‐19 treatment in the context of predictive, preventive, and personalized medicine in virus‐related diseases.